Informella sittplatser i det offentliga stadsrummet - Persson, Therese (2009)
This thesis is about informal seatings, those which are planned to merge into the city core environment and to supply a flexible public space. The thesis discusses how a diverse range of elements could result in different functions and social meanings. These are illustrated with visual examples and conceptual drawings. The position of the seating in a small public place is important, as well as its location in the city. Furthermore, the detail design of the seating, such as the form and dimensions have to be considered in order to create an informal seating appropriate for the user. This leads to the broad scope of this thesis which deals with the small scale - how the seatings can create a good environment in a small place; and the big scale - how a site can influence the city. This thesis suggests the physical design of some informal seatings and also investigates how these seatings can strengthen the place through their function and how they relate to their surroundings. This includes an analysis of what attracts people to the site, such as what facilities are close by and how the microclimate can affect the orientation of the seatings. The site of my proposal is currently used as a parking lot on Stora Gråbrödersgatan, situated in the city centre of Lund.